A study of a long duration B9 flare-CME event and associated shock - Chandra R.; Chen P.F.; Fulara A.; Srivastava A.K.; Uddin W. (My University, 2025)
We present and discuss here the observations of a small long duration GOES B-class flare associated with a quiescent filament eruption, a global EUV wave and a CME on 2011 May 11. The event was well observed by the Solar Dynamics Observatory (SDO), GONG Hα STEREO and Culgoora spectrograph. As the filament erupted, ahead of the filament we observed the propagation of EIT wave fronts, as well as two flare ribbons on both sides of the polarity inversion line (PIL) on the solar surface. The observations show the co-existence of two types of EUV waves, i.e., a fast and a slow one. A type II radio burst with up to the third harmonic component was also associated with this event. The evolution of photospheric magnetic field showed flux emergence and cancellation at the filament site before its eruption. © 2017 COSPAR